Evaluation of a Diagnostic Method to Quantify Aflatoxins B1 and M1 in Animal Liver by High-Performance Liquid Chromatography with Fluorescence Detection. (3rd December 2019) - Du, Xiangwei; Schrunk, Dwayne E; Imerman, Paula M; Smith, Lori; Francis, Kyle; Tahara, John; Tkachenko, Andriy; Reimschuessel, Renate; Rumbeiha, Wilson K
Abstract: Background: Aflatoxins (AFs) are secondary metabolites of fungi and are one of the causes of toxin-related pet food recalls. An intralaboratory method was previously developed to quantify aflatoxin B1 (AFB1 ) and aflatoxin M1 (AFM1 ) in animal liver by HPLC with fluorescence detection. Objective: The aim of this study was to extensively evaluate the method performance with a single-laboratory blinded method test (BMT-S) and a multilaboratory blinded method test (BMT-M). Methods: Blinded tissue samples were prepared by a third-party laboratory and sent out to participating laboratories for both BMT-S and BMT-M. Results: In both tests, participants analyzed blinded samples prepared by an independent laboratory. In the BMT-S, accuracy ranged between 111 and 154% for AFB1 and 113 and 159% for AFM1 within the quantitation range of 0.1–0.5 ng/g. The HorRat values for repeatability ranged between 0.1 and 0.3 for AFB1 and 0.3 and 0.6 for AFM1 . In the BMT-M, the interlaboratory accuracy ranged between 77 and 81% for AFB1 and 83 and 85% for AFM1 within the quantitation range of 0.2–10 ng/g. The HorRat values for reproducibility ranged between 0.4 and 0.7 for AFB1 and 0.4 and 0.9 for AFM1 . Both recovery and reproducibility were acceptable. Conclusions: BMT-M evaluation demonstrated that the method was suitable for quantitation of aflatoxins B1 and M1 in animal liver between laboratories. Highlights: The BMT-S and BMT-M results demonstrated that the method is rugged and reproducible among the participating laboratories.